The Effect of the Tapering on the Concentration of Some Plasma Cytokines and Physical Performance in Endurance Male Runners - N Farhangi (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Moderate exercise training improves immune system function, but intensive and prolonged bouts of endurance training weaken immune function. Some athletes reduce their training load for 6-21 days before the major competitions. The purpose of this research was to investigate the effect of 7 and 21 days tapering period length on the concentrations of some plasma immunological factors and performance time in endurance male runners. METHODS: This semi experimental study was performed on 22 well trained male runners with aged 24.5 ± 2.6 years. Before the beginning of exercise trainings, the subjects were randomly divided into two groups (control and taper). The blood samples were taken 1 and 3 days before the beginning of training and after 4, 8, 9, and 11 weeks training, immediately after 10 km treadmill test. IL-1β and IL-6 levels were assayed by using a validated commercial ELISA (Quantikine Minneapolis, MN) and compared together.FINDINGS: With comparison IL-1β and IL-6 concentrations and performance time between groups, after 11 weeks training, there were significant decreases in IL-1β and IL-6 concentrations and performance time in the taper group in comparison with control group (p<0.001, p<0.001, p<0.001). CONCLUSION: According to the research results, during three week taper period, decreasing of training volume of the taper group in proportion to control group one can reduce IL-1β and IL-6 concentrations without having disorder on performance time. It is likely because of the muscle myocyte injury decrease in athletes body. Therefore coaches regarding caution can use 2 to 3 week taper period for improving of athletic performance.